Variantes genéticas envolvidas no metabolismo do folato: impacto na carcinogênese de cabeça e pescoço - Silva, Lidia Maria Rebolho Batista (2010)
Introduction: Head and neck cancer is a collective term defined by anatomical and topographical basis to describe malignant tumors of the upper aerodigestive tract. This anatomical region includes the oral cavity, pharynx and larynx, having as the main risk factors smoking and alcoholism. The most representative hystologic type from head and neck cancer was squamous cell carcinoma (HNSCC), with more than 500,000 new cases worldwide every year. Folate deficiency is associated with increased risk of several types of cancer and alterations in folate metabolism may contribute to the process of carcinogenesis by influencing DNA methylation and genomic stability. Polymorphisms in genes encoding enzymes involved in this pathway may alter enzyme activity and consequently interfere in concentrations of homocysteine and Sadenosylmethionine that are important for DNA synthesis and cellular methylation reactions. Objectives: Investigate MTHFD1 G1958A, BHMT G742A, TC2 C776G and TC2 A67G polymorphisms involved in folate metabolism on head and neck cancer risk, and the association between these polymorphisms with primary site, tumor extension, lymph node involvement and prognosis of the disease. Patients and Methods: Were included in the study 694 individuals (240 patients with head and neck cancer and 454 controls). Molecular analysis was made by genomic DNA from peripheral blood and genetic alterations were investigated by Polymerase Chain Reaction-restriction Fragment Length Polymorphism (PCR-RFLP) and Real Time-PCR. Socio-demographic data were obtained from patient´s medical records and interview of the controls. Results: Multiple logistic regression showed that tobacco, alcohol and age over 42 years were predictors for the disease (P<0.05). Hardy-Weinberg equilibrium showed that the genotypic distributions were in equilibrium for both groups in all polymorphisms studied. The MTHFD1 1958GA or AA genotypes associated with tobacco (P=0.04) and alcohol (P=0.03) consumption increase the risk for head and neck cancer (HNSCC). These same genotypes were found in higher proportion in patients with advanced stage tumors (P=0.04) and in patients with lower survival (P=0.01). TC2 C776G polymorphism (P=0.03) were less frequent in patients with age over 52 years and TC2 A67G polymorphism (P=0.04) were less frequent in patients with 52-63 years. TC2 C776G polymorphism was not associated to HNC, however was present in higher proportion in patients with pharynx as primary site of tumor (P=0.02). Conclusions: Are predictors for head and neck cancer, regardless of the gene, tobacco and alcohol consumption and age over 42 years. The presence of MTHFD1 G1958A polymorphism associated to tobacco and alcohol consumption may modulate the risk for disease development.